2020
DOI: 10.1021/acsomega.9b04465
|View full text |Cite
|
Sign up to set email alerts
|

Copper-Ion-Assisted Precipitation Etching Method for the Luminescent Enhanced Assembling of Sulfur Quantum Dots

Abstract: In this study, we report a metal-ion-assisted precipitation etching strategy that can be used to manipulate the optical properties associated with the assembling of sulfur quantum dots (S dots) using copper ions. Transmission electron microscopy confirmed that the S dots were mainly distributed within 50−80 nm and that they exhibited an ambiguous boundary. After the post-synthetic Cu 2+ -assisted modification was completed, the assisted precipitation-etching S dots (APE-S dots) were observed to exhibit a relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 26 publications
1
23
0
Order By: Relevance
“…However, they did not receive intensive attention until Shen and co‐workers reported the use of elemental sulfur to prepare SQD in 2018 [21] . In the past two years, impressive progress has been made in the synthesis of luminescent SQDs from elemental sulfur, including increasing PLQY (from 3.8 % to about 50 %), shortening reaction time (from 125 h to 4 h) and increasing reaction yield (from 0.87 % to 5.08 %) [23–32] . However, considering the practical applications of SQDs, there are still some important issues that need to be addressed.…”
Section: Synthetic Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…However, they did not receive intensive attention until Shen and co‐workers reported the use of elemental sulfur to prepare SQD in 2018 [21] . In the past two years, impressive progress has been made in the synthesis of luminescent SQDs from elemental sulfur, including increasing PLQY (from 3.8 % to about 50 %), shortening reaction time (from 125 h to 4 h) and increasing reaction yield (from 0.87 % to 5.08 %) [23–32] . However, considering the practical applications of SQDs, there are still some important issues that need to be addressed.…”
Section: Synthetic Methodsmentioning
confidence: 99%
“…In addition to H 2 O 2 , Li et al reported the use of Cu 2 + to enhance the PLQY of SQDs based on the post-etching treatment. [31] Similar to that of H 2 O 2 treatment, Cu 2 + was added to the aqueous dispersion of SQDs precursor, which was prepared according to the Shen's report. The PLQY of SQDs after treatment by Cu 2 + could reach as high as 32.8 %.…”
Section: Post-etching Synthesismentioning
confidence: 99%
See 3 more Smart Citations